Konsep Banān dalam QS Al-Qiyāmah Ayat 3–4 Perspektif Tafsir al-Jawāhir dan Relevansinya dengan Biometrik Modern - Amanda Utari; Khoirun Nidhom; Mohamad Mualim (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2026)
The Qur'an, as the holy book of Muslims, contains scientific allusions whose relevance to modern scientific developments continues to be studied. One such allusion is found in QS. Al-Qiyāmah verses 3–4, specifically in the mention of the term banān (fingertips), which is often associated with the concept of fingerprints in modern biometrics. This study aims to analyze Ṭanṭāwī Jawharī's interpretation of these verses in Tafsir al-Jawāhir and to examine its relevance to contemporary biometric technology. The research employs a library research method with a thematic exegesis approach (mauḍū‘ī) and descriptive-analytical analysis. The primary data sources are QS. Al-Qiyāmah verses 3–4 and Ṭanṭāwī Jawharī's Tafsir al-Jawāhir. The results reveal that Ṭanṭāwī Jawharī interpreted the term banān as a symbol of the perfection and precision of human creation, demonstrating Allah's power to resurrect humans in complete form. The scientific exegesis style he employed opens a space for contextual understanding, wherein the mention of fingertips can be perceived as an allusion to the uniqueness of human biological identity, which has since been scientifically proven through fingerprint technology in modern biometric systems. This relevance highlights the dimension of i'jāz 'ilmī (scientific inimitability) within the verse. Nevertheless, this study emphasizes that the relationship between the verse and science must be understood proportionally as a reflective correlation, rather than an apologetic attempt to fit sacred text to scientific theory, thereby preserving the primary function of the Qur'an as a book of guidance.